The Relationship of Family Social Support with Loneliness in the Elderly - Syaharuddin Syaharuddin; Siti Utami Dewi; M. Khalid Fredy Saputra; Qalbia Muhammad Nur; Chaedyr Iqbal (Jurnal Edukasi Ilmiah Kesehatan, 2023)
Aging brings several significant changes in a person's life, and one of the main challenges older people face is loneliness. Loneliness can have a profound impact on the mental and physical well-being of seniors, increasing the risk of mental illness, lowering quality of life, and even accelerating the aging process. This study aims to determine the relationship between family social support and loneliness in older people. The research approach used is a quantitative research approach with correlative descriptive. The population in this study was 42 more senior people, all of whom were elderly. The sample in this study was 42 older adults who met the inclusion and exclusion criteria. In this study, the technique used was the total sampling technique. The results of statistical tests conducted with Chi-square obtained a p-value of 0.1000, informational support p-value of 0.758; reward support a p-value of 0.115, emotional support p-value of 0.767, instrumental support can be concluded that social support from family plays a vital role in influencing the level of loneliness in older people. Families that provide emotional, physical, and social support can help create a supportive environment, strengthen social bonds, and reduce the risk of loneliness in later stages